Cognitive disorders and dementia in patients on hemodialysis (Engrami, 2021)
Patients on hemodialysis are at increased risk of cognitive decline and the development of dementia. The course and nature of chronic renal failure are risk factors for cognitive decline. In addition, patients on hemodialysis are exposed to frequent hemodynamic stresses that affect cerebral perfusion to which they are particularly vulnerable due to frequent comorbidities that carry cardiovascular risk. Metabolic abnormalities, acid-base imbalances, water and electrolyte imbalances, inflammation and oxidative stress, and the accumulation of toxic substances that act as risk factors for cognition disorders are also common in this population. Adequate cognitive functioning of these patients is essential in order for them to be able to take care of their health and adopt medical advice, and to have the best possible quality of life. For these reasons, early detection of factors that lead to cognitive dysfunction in this population and right time intervention are very important to alleviate these risk factors.
Keywords: dementia; cognitive disorders; hemodialysis